A comprehensive review on nutraceutical potential of underutilized cereals and cereal-based products - Mahek Rawat; Aditi Varshney; Muskan Rai; Aniket Chikara; Arvandana Liza Pohty; Akanksha Joshi; Anjali Binjola; Chandra Pratap Singh; Kamna Rawat; Muzamil Ahmad Rather; Arun Kumar Gupta (Journal of Agriculture and Food Research, 2023)
Cereals provide nutrients such as lipids, carbs, proteins, minerals, and vitamins and make up the majority of human nutrition. Some cereals also contain a significant quantity of dietary fiber (soluble and insoluble). Cereals, when consumed as a whole or in coloured varieties, are the source of bioactive components with functional properties. Dietary fiber in whole grains has a unique blend of bioactive components such as resistant starch, vitamins, minerals, phytochemicals, and antioxidants that provide different health benefits. Traditionally, whole grains were consumed, but currently, most foods are derived from refined fractions of cereal and pulse crops. Minimal processing of cereals increases both nutrient bioavailability and health benefits. The bioactive compounds present in whole cereals ultimately fight against diseases and prevent or control some diseases in the body, such as cardiovascular risk, reducing the risk of cancer, type-2 diabetes, hypertension, and high blood pressure, improving gastrointestinal health, etc. The consumer demands minimally processed foods, which are essential for maintaining health and improving metabolism. Therefore, developing products using whole cereals or millet to improve the health and safety of humans is of great interest. The present review discusses the nutraceutical potential of cereals and their products, their impact on gut microbiota, and consumer acceptability. The potential for future research in the processing of such healthy cereals in combination with other pseudocereals is identified and discussed.